Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

An experimental investigation on aspects of infectious salmon anaemia virus (ISAV) infection dynamics in seawater Atlantic salmon, Salmo salar L. - A Gregory; L A Munro; M Snow; K L Urquhart; A G Murray; R S Raynard (Journal of Fish Diseases, 2009)
This study investigated infection dynamics of infectious salmon anaemia virus (ISAV) by conducting two experiments to examine minimum infective dose and viral shedding of ISAV. In terms of minimum infective dose, the high variability between replicate tanks and the relatively slow spread of infection through the population at 1 × 10 1 TCID 50 mL −1 indicated this dose is approaching the minimum infective dose for ISAV in seawater salmon populations. A novel qPCR assay incorporating an influenza virus control standard with each seawater sample was developed that enabled the quantity of ISAV shed from infected populations to be estimated in values equivalent to viral titres. Viral shedding was first detected at 7 days post‐challenge (5.8 × 10 −2 TCID 50 mL −1 kg −1 ) and rose to levels above the minimum infective dose (4.2 × 10 1 TCID 50 mL −1 kg −1 ) on day 11 post‐challenge, 2 days before mortalities in ISAV inoculated fish started. These results clearly demonstrate that a large viral shedding event occurs before death. Viral titres peaked at 7.0 × 10 1 TCID 50 mL −1 kg −1 15 days post‐infection. These data provide important information relevant to the management of ISA.

Estimation of infectious dose and viral shedding rates for infectious pancreatic necrosis virus in Atlantic salmon, Salmo salar L., post‐smolts - K Urquhart; A G Murray; A Gregory; M O’Dea; L A Munro; D A Smail; A M Shanks; R S Raynard (Journal of Fish Diseases, 2008)
Infectious dose and shedding rates are important parameters to estimate in order to understand the transmission of infectious pancreatic necrosis virus (IPNV). Bath challenge of Atlantic salmon post‐smolts was selected as the route of experimental infection as this mimics a major natural route of exposure to IPNV infection. Doses ranging from 10 2 to 10 −4 50% end‐point tissue culture infectious dose (TCID 50 ) mL −1 sea water were used to estimate the minimum infectious dose for a Scottish isolate of IPNV. The minimum dose required to induce infection in Atlantic salmon post‐smolts was −1 TCID 50 mL −1 by bath immersion (4 h at 10 °C). The peak shedding rate for IPNV following intraperitoneal challenge using post‐smolts was estimated to be 6.8 × 10 3 TCID 50 h −1 kg −1 and occurred 11 days post‐challenge. This information may be incorporated into mathematical models to increase the understanding of the dispersal of IPNV from marine salmon sites.

Distribution of infectious pancreatic necrosis virus (IPNV) in wild marine fish from Scottish waters with respect to clinically infected aquaculture sites producing Atlantic salmon, Salmo salar L. - I S Wallace; A Gregory; A G Murray; E S Munro; R S Raynard (Journal of Fish Diseases, 2008)
This study represents the first large‐scale investigation of IPNV in Scottish wild marine fish. Kidney samples were taken from 30 627 fish comprising 37 species and 45 isolations were made from nine different species, illustrating these as reservoirs of IPNV in Scottish waters. The estimated prevalence of IPNV in the Scottish marine environment was low at 0.15% (90% confidence intervals, (CI) of 0.11–0.19%). This was significantly greater in fish caught less than 5.0 km from IPN‐positive fish farms in Shetland, at 0.58% (90% CI of 0.45–0.77%). This prevalence persisted and did not significantly decrease over the 16‐month period of study. The estimated prevalence of IPNV for each positive species was less than 1% with the statistically non‐significant exceptions of flounder, Platichthys flesus (L.), at 12.5% (90% CI of 0.64–47.06%) and saithe, Pollachius virens (L.), at 1.11% (90% CI of 0.49–2.19%). The 45 isolates were titrated and all but two were below the detection limit of the test ( −1 ). Titres of 3.8 × 10 2 PFU g −1 and 2.8 × 10 1 PFU g −1 were calculated from common dab, Limanda limanda (L.), and saithe, respectively. This study provides evidence that clinical outbreaks of IPN in farmed Atlantic salmon may cause a localized small increase in the prevalence of IPNV in wild marine fish.

Genetic analysis of infectious pancreatic necrosis virus from Scotland - N Bain; A Gregory; R S Raynard (Journal of Fish Diseases, 2008)
Infectious pancreatic necrosis (IPN) is a highly contagious disease of young salmonid fish, and is one of the most serious economic diseases in aquaculture. In Scotland, an increase in IPN virus (IPNV) outbreaks in seawater Atlantic salmon, Salmo salar , has been reported in recent years. The aim of this study was to analyse the VP2 gene from recent IPNV isolates from Scotland, to determine whether there are epidemiological links between IPNV isolates from farms (13), wild fish (17) and the environment (6) in order to investigate potential wild and farmed fish interactions. Comparison of the nucleotide sequence of the VP2 gene revealed that 34 of 36 isolates were 97.1–100% similar and the deduced amino acid sequences showed 97–100% identity. Two isolates from wild fish exhibited the most divergence at 85–87.3% similarity to the other isolates at the nucleotide level and 88.2–90.8% identity at the deduced amino acid level. Phylogenetic analyses revealed that 34 of 36 of the isolates from Scotland were genetically closely related to the A2 (Sp) serotype of IPNV. The two wild isolates from seatrout, Salmo trutta , and flounder, Platichthys flesus , were most closely related to the European A5 (Te) serotype. This study represents a comprehensive IPNV phylogenetic study that indicates that there are closely related or identical isolates in circulation in the marine environment, which adds evidence that disease interactions between wild and farmed fish may occur. This type of analysis is a useful tool in the management and control of fish diseases because it can assist in the identification of epidemiological links and highlight potential risks to aquaculture.

Detection of infectious pancreatic necrosis virus (IPNV) from the environment in the vicinity of IPNV‐infected Atlantic salmon farms in Scotland - A Gregory; L A Munro; I S Wallace; N Bain; R S Raynard (Journal of Fish Diseases, 2007)
Infectious pancreatic necrosis virus (IPNV) has been isolated from mussels, sediment and surface water in the vicinity of clinically infected salmon farms, at shore bases supplying the farms and for several hundred metres distance from farms in the direction of current flow. There was evidence of decreasing prevalence of IPNV in mussels from Shetland once IPN outbreaks subsided, indicating they are an unlikely source of re‐infection on farms. There was little evidence of persistence in the environment, although conclusions were complicated by the presence of IPNV on neighbouring farms 1 year after the outbreak.

Experimental susceptibility of Atlantic cod, Gadus morhua (L.), and Atlantic halibut, Hippoglossus hippoglossus (L.), to different genotypes of viral haemorrhagic septicaemia virus - M Snow; J A King; A Garden; R S Raynard (Journal of Fish Diseases, 2005)
Viral haemorrhagic septicaemia (VHS) is a well‐characterized disease of rainbow trout, Oncorhynchus mykiss , which has also caused economic losses in marine turbot farms in the British Isles. We have previously demonstrated that turbot, Scophthalmus maximus , are susceptible to isolates of viral haemorrhagic septicaemia virus (VHSV) that are endemic in the marine environment, highlighting a potential risk to marine aquaculture. Given the increasing interest in the intensive rearing of additional aquaculture species such as Atlantic cod, Gadus morhua , and Atlantic halibut, Hippoglossus hippoglossus , this study aimed at investigating the susceptibility of these species to VHSV. Both species were found to be largely resistant to VHS following immersion challenge with a selection of 18 isolates, representing the known marine VHSV genotypes. Only one and two VHSV‐associated mortalities occurred out of a total of 1710 and 1254 halibut and cod, respectively. These findings suggest that there is a low direct risk to the development of commercial cod and halibut aquaculture from the existing endemic reservoir of VHSV. This study, coupled to field observations has, however, highlighted the fact that both species can become infected with VHSV. The known adaptability of RNA viruses, together with the selection pressures associated with intensive aquaculture would thus advocate a cautious approach to VHSV surveillance within these emerging industries.

An evaluation of current diagnostic tests for the detection of infectious salmon anaemia virus (ISAV) following experimental water‐borne infection of Atlantic salmon, Salmo salar L. - M Snow; R S Raynard; A G Murray; D W Bruno; J A King; R Grant; I R Bricknell; N Bain; A Gregory (Journal of Fish Diseases, 2003)
Four commonly used diagnostic tests [reverse transcription polymerase chain reaction (RT‐PCR), indirect fluorescent antibody test (IFAT), virus culture and light microscopy] were evaluated for their ability to detect infectious salmon anaemia virus (ISAV) or tissue pathology following experimental infection of Atlantic salmon. Fish were infected with ISAV by water‐borne exposure which mimics the route of natural infection. Forty‐five per cent of pre‐clinical fish tested yielded positive results by RT‐PCR for at least one of the organs tested (kidney, heart, gill, liver, blood). No significant difference was detected between organs in the number or time of first occurrence of positive result. Virus culture identified a total of 14% of pre‐clinical fish as ISAV‐infected. The presence of ISAV in heart tissue was particularly notable (13% of fish sampled) as was the inability to culture virus from spleen tissue. In the case of IFAT, 15% of fish sampled were positive, although tissue other than kidney proved unsuitable for use in this method. Only limited ISAV‐specific pathology was detectable by histological examination of fish prior to the onset of clinical disease. These findings reveal important information regarding the optimal choice of both tissue sample and diagnostic test for the routine diagnosis of ISAV.

Studies on the use of hydrogen peroxide as a method for the control of sea lice on Atlantic salmon - D. W. Bruno; R. S. Raynard (Aquaculture International, 1994)